Competitiveness in research and development comparisons and performance - Török, Ádám 1952-; Telcs, András; Borsi, Balázs (Edward Elgar, 2005)
Competitiveness in Research and Development includes a unique comparative analysis of R&D and innovation systems of transition and developing economies. It also features a comprehensive and critical survey of international literature on the measurement of R&D and innovation performance
Includes bibliographical references and index
Keywords: Forschung und Entwicklung; Technische Innovation; Wettbewerbsfähigkeit; Technological innovations / Economic aspects / Hungary; Research / Economic aspects / Hungary; Technological innovations / Economic aspects / Developing countries; Research / Economic aspects / Developing countries; Comparative economics; Competition